PENELITIAN NILAI KALOR BAHAN BAKAR BIOMASSA PADA LIMBAH KOTORAN HEWAN - Sunaryo -; Wahyu Widiatmo (Jurnal APTEK, 2014)
Biomass is the dry matter of organic material . Biomass is very important as a potential source ofenergy ( fuel ) . Very important properties of the fuel is the calorific value . Thus it is necessary forthe determination of calorific value by means of testing and then applied to the correlations existingtechnologies to be developed in further research . In this study the type of waste biomass is derivedfrom animal manure is manure , bat droppings , and goat manure . Tests performed with gaugescalorific value of biomass fuels Calorimeter . Further test results compared to the results of theestimation using correlation . Value for the test sample size of cow dung 10.90874 MJ / kg , goatdung 10.37851 MJ / kg and bat droppings of 17.09983 MJ / kg . In general, the closest correlationstudy of three kinds of sample average animal waste biomass fuel is obtained correlation Beckmanwith an average difference of 3.88 %.